The importance of tree internal water storage under drought conditions. (2nd November 2021) - Preisler, Yakir; Hölttä, Teemu; Grünzweig, José M; Oz, Itay; Tatarinov, Fedor; Ruehr, Nadine K; Rotenberg, Eyal; Yakir, Dan
Abstract: Global warming and drying trends, as well as the increase in frequency and intensity of droughts, may have unprecedented impacts on various forest ecosystems. We assessed the role of internal water storage (WS) in drought resistance of mature pine trees in the semi-arid Yatir Forest. Transpiration ( T ), soil moisture and sap flow (SF) were measured continuously, accompanied by periodical measurements of leaf and branch water potential (Ψleaf ) and water content (WC). The data were used to parameterize a tree hydraulics model to examine the impact of WS capacitance on the tree water relations. The results of the continuous measurements showed a 5-h time lag between T and SF in the dry season, which peaked in the early morning and early afternoon, respectively. A good fit between model results and observations was only obtained when the empirically estimated WS capacitance was included in the model. Without WS during the dry season, Ψleaf would drop below a threshold known to cause hydraulic failure and cessation of gas exchange in the studied tree species. Our results indicate that tree WS capacitance is a key drought resistance trait that could enhance tree survival in a drying climate, contributing up to 45% of the total daily transpiration during the dry season.